IDEATIONAL MEANING OF TRADITIONAL WEDDING CEREMONY HORJA HAROAN BORU TAPANULI SELATAN - Daulay, Irma Khoirot; Saragih, Amrin; Husein, Rahmad (Association of Language Teachers in Southeast Asia (ALTSA), 2020)
This study was aimed at finding out the ideational meaning on traditional wedding ceremony Horja Haroan Boru Tapanuli Selatan (HHBTS) and to elaborate the reason for the use of verbal components from three side namely Mora, Kahanggi and Anak boru. The analysis of this studyused qualitative analysis, and the theory used was from M.A.K. Halliday (1985, 1994 and 2004). This study found that the language being used by three participants (Kahanggi, Mora and Anakboru) namely; Kahanggi is dominantly used material activities, Mora and anakboru are dominantly used Mental and behavioral activities. Moreover, these three participants shows their position while Kahanggi as the host of the ceremony, anakboru as the supporter who take the responsibility in preparing the stuff in every steps of ceremony, while mora has the power to give advice, suggestion, permission and rejection in that ceremony